Optic Nerve Head Hemoglobin Levels in Glaucoma: A Structural and Functional Correlation Study - Janaina A. G. Rocha; Diego T. Dias; Maria Betânia C. Lemos; Fábio N. Kanadani; Augusto Paranhos; Carolina P. B. Gracitelli; Tiago S. Prata (Journal of Ophthalmology)
Purpose. To investigate structural and functional correlations in glaucoma patients using optic nerve head hemoglobin (ONH Hb) measurements as determined by automated colorimetric analysis of conventional retinography. Methods. We prospectively enrolled healthy participants and glaucomatous patients with a wide range of disease stages. All participants underwent visual field (VF) testing (standard automated perimetry, SAP), color fundus imaging (mydriatic retinography), and peripapillary retinal nerve fiber layer (pRNFL) assessment through spectral-domain optical coherence tomography (SD-OCT). Software Laguna ONhE was used to estimate the amount of ONH Hb and to determine the glaucoma discriminant function (GDF) index. Scatter plots were constructed, and regression analysis was used to investigate the correlations between GDF, average pRNFL thickness, and VF mean deviation (VFMD) index values. A secondary analysis was performed to compare each parameter between three different glaucoma groups divided according to VFMD values (mild, >−6 dB; moderate, −6 to −12 dB; and advanced, <−12 dB). Results. One hundred ninety-six eyes from 123 participants (69 with glaucoma and 54 controls) were enrolled. Overall, all parameters evaluated differed significantly between glaucomatous and control eyes (p≤0.001). The comparison of each parameter according to groups of disease stages revealed significant differences between controls and each of the glaucomatous groups (p<0.001). More pronounced changes in GDF values were observed in early disease stages. We found significant nonlinear correlations between GDF and VFMD values (R2 = 0.295, p<0.001) and between pRNFL thickness and VFMD (R2 = 0.598, p<0.001). A linear correlation was found between GDF and pRNFL thickness values (R2 = 0.195, p<0.001). Conclusion. Our results showed significant associations between ONH Hb values and both structural and functional damage in glaucoma obtained by SD-OCT and SAP, respectively. The nonlinear correlation we found and the GDF behavior along different disease stages suggest that ONH Hb levels’ reduction may precede visual function changes in early glaucoma stages.